Actual problems of protection of social and labor rights of employees - Belkhozhayeva, D.Zh.; Baisymakova, D.S. (Bulletin of the Karaganda University “Law Series”, 2021)
The urgency of the problem of protecting the social and labor rights of employees is associated with the lack of attention to this problem on the part of the science of labor law and the circumstance of legislation that does not meet the needs of practice, the basics of non-positive solutions to the problem of protecting social and labor rights in practice, requiring comprehensive improvement of the legal regulation of the relevant relations. The study showed that the violation of social and labor rights of employees in society, especially in connection with the payment of wages and working conditions, occurs when applying for employment or dismissal. However, most of them do not go anywhere and do not seek to protect their social and labor rights, which indicates both the passivity of citizens and their low level of trust in the authorities and public organizations designed to protect the social and labor rights and interests of the employee. In this regard, the purpose of the article is a theoretical analysis of the protection of social and labor rights and interests of employees, determining the place of protection of social and labor rights in the mechanism of legal regulation of social and labor relations. In addition, an analysis of the effectiveness of legal remedies for the protection of violated social and labor rights at the current stage of development of labor relations can be highlighted as an objective. Analyzing the effectiveness of existing methods of restoring violated labor rights, the article also addresses the problem of resolving labor disputes through judicial protection. As a result of the study, the authors conclude that it is necessary to improve labor legislation in the field of protection of social and labor rights of employees.